Sex-specific differences in the clinical profile among psychiatric patients with pulmonary Embolism: a hospital-based retrospective study - Kong, Lanlan; Lu, Yueying; Han, Dongsheng; Liu, Ting; Bai, Yuanhan (BMC pulmonary medicine, 2024)
Pulmonary embolism (PE) is a severe and life-threatening complication of venous thromboembolism. However, there is a lack of systematic studies on differences between female and male PE patients. This paper aimed to compare the sex-specific differences in clinical characteristics and laboratory indicators in psychotic patients with PE. This retrospective study enrolled psychiatric patients with PE from June 2018 to June 2022 at Shenzhen Kangning Hospital (Shenzhen Mental Health Center). Demographic characteristics, factors associated with PE, and laboratory indices were collected to assess sex-specific differences. Of the 168 patients, 87 (51.8%) were female and 81 (48.2%) were male, with a mean age of 58 years for females and 46 years for male patients. The male group had higher ratio of hyperprolactinemia, more patients using antipsychotic medications, higher D-dimer levels at PE onset, greater D-dimer difference, and a higher rate of D-dimer elevation than the female group (p < 0.05). Female patients were significantly older, exhibited a higher prevalence of diabetes, and had a greater number of patients taking antidepressants and hypnotics/sedatives than male patients (p < 0.05). Schizophrenia spectrum disorders were more prevalent in male patients, while female patients had a higher incidence of mood disorders (p < 0.05). Among patients aged < 45 years, the male group had higher D-dimer levels at PE onset and greater D-dimer difference (p < 0.05). Among all 112 patients aged ≥ 45 years, male patients were more likely than female patients to have respiratory tract infections, higher D-dimer levels at PE onset, greater D-dimer difference, and a higher rate of D-dimer elevation (p < 0.05). The multiple linear regression analysis indicated that hyperprolactinemia and the use of first-generation antipsychotics (FGAs) were associated with D-dimer levels at PE onset in male patients, while the time of PE onset and protective restraints were associated with D-dimer levels at PE onset in female patients (p < 0.05). PE-associated clinical features differ between male and female patients. These differences may imply that the processes and mechanisms of PE onset are sex specific. Male patients are more likely to have respiratory tract infections and higher D-dimer levels at PE onset than female patients. The use of FGAs may be associated with increased D-dimer in male psychiatric patients, while protective restraints may be associated with increased D-dimer in female psychiatric patients.